The Media in Scotland - Blain, Neil (Edinburgh University Press, 2022)
GBS_insertPreviewButtonPopup('ISBN:9780748628001');This book brings together academics, writers and politicians to explore the range and nature of the media in Scotland. The book includes chapters on the separate histories of the press, broadcasting and cinema, on the representation and construction of Scotland, the contemporary communications environment, and the languages used in the media. Other chapters consider television drama, soap opera, broadcast comedy, gender, the media and politics, race and ethnicity, gender, popular music, sport and new technology, the place of Gaelic, and current issues in screen fiction. Among the contributors are David Bruce, Myra Macdonald, Brian McNair, Hugh O'Donnell, Mike Russell, Philip Schlesinger and Brian Wilson.Key FeaturesThe first comprehensive picture of the media in ScotlandRaises a number of important questions about how Scotland presents itself at home and abroadAnalyzes questions of politics, economics and governance.